PERSPEKTIF HUKUM ISLAM TERHADAP HUKUMAN MATI BERDASARKAN UNDANG-UNDANG TERKAIT HAK ASASI MANUSIA DI INDONESIA - Ayusriadi Ayusriadi; Abdul Razak; Muh Arfin Hamid (Fakultas Hukum Universitas Riau, 2018)
This research was aimed at finding out and elaboration the perspective of Islamic Law on the capital punishment based on the human rights laws taking into force in Indonesia. This research was a normative legal research using statutory, conceptual and comparative approaches. The legal sources were collected through literature study. The collected legal sources were analyzed by using rules of law, relativism and human rights and Islamic law maslahah theoryes in order to find out the perspective of Islamic law and the human rights against the capital punishment in order to make legal prescriptions on the discussed legal problem. The research results indicated that the perspective between Islamic law and the human rights on the capital punishment could be matched. In Islamic law is explicitly states that the capital punishment is a must in the crime of murder, whereas according to the concept of human rights, especially the international world that the dominated by western country, states that the capital punishment is not recommended because it violats a person’s right to live as God's gift. The capital punishment it self in the concept of human rights has two dimensions, namely the universal dimension and the particular dimension. The Particular dimension state that the human rights enforcement is returned to each countries. This dimension is in line with the ideas of Islamic law as long as it suitable with the proportion of harm and its benefits. The values of human rights, especially in Indonesia, are born from the noble values of a nation so that they may have different views on the necessary of the capital punishment. The decisions on the capital punishment are returned to each country.